PEMANFAATAN LIMBAH LIDAH BUAYA SEBAGAI FEED SUPPLEMET PAKAN SAPI BALI DALAM UPAYA MENGURANGI EMISI METAN - I.G. Mahardika; N.N. Suryani; N.P. Mariani; I.W. Suarna; M.A.P. Duarsa; I.M. Mudita (Udayana University)
Waste of Aloevera is one of the agriculture wastes which have highly potential for Bali cattle feed supplement, so that research in order to learn the effect of supplementation of Aloevera as High Quality Feed Supplement (HQFS) is needed. Twenty male Bali cattle were used in this experiment, which weight range between 191 – 232 kg. Feed for cattle consisted of rice straw, concentrate and feed supplement in form of Hight Quality Feed Supplement (HQFS) which mixed from sea grass and waste of aleovera. Randomized Block Design was applied in this experiment with 4 repetitions. Treatment A was ad lib of rice straw + 2 kg of concentrate, Treatment B was ad lib of rice straw + 2 kg of concentrate + 150 g HQFS, Treatment C was ad lib of rice straw + 2.5 kg of concentrate + 150 g HQFS, Treatment D was ad lib of rice straw + 3 kg of concentrate + 150 g HQFS and Treatment E was ad lib of rice straw + 3 kg of concentrate. Results of this experiment showed that supplementation of HQFS tended to decrease feed consumption and methan production, meanwhile supplementation of HQFS could increase diets efficiency and therefore increased the growth of cattle. HQFS supplementation gave more effective response at lower quality diets meanwhile in good quality diets gave no positive effect.